2014
DOI: 10.3109/09513590.2014.994601
|View full text |Cite
|
Sign up to set email alerts
|

History of biochemical pregnancy was associated with the subsequent reproductive failure among women with recurrent spontaneous abortion

Abstract: The aim of this study was to evaluate whether the presence of history of biochemical pregnancy (BP) was associated with clinical characteristics and the subsequent pregnancy outcome among women with recurrent spontaneous abortion (RSA). One-hundred and seventy-five RSA women with two or more clinical pregnancy losses were enrolled. The clinical characteristics were compared between 164 women with history of 0-1 BP (Group A) and 11 women with two or more BP (Group B). The frequency of previous pregnancy loss an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Biochemical pregnancy is defined in similar terms by a variety of authors. Maesawa uses the International Committee Monitoring Assisted Reproductive Technologies and World Health Organization definition for biochemical pregnancy as the detection of hCG in blood or urine without subsequent clinical signs of pregnancy [ 9 ]. Coulam defines biochemical pregnancy when two or more increased values of hCG can be measured, yet there can be no evidence of gestational sac detected on transvaginal ultrasound 2 weeks later.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochemical pregnancy is defined in similar terms by a variety of authors. Maesawa uses the International Committee Monitoring Assisted Reproductive Technologies and World Health Organization definition for biochemical pregnancy as the detection of hCG in blood or urine without subsequent clinical signs of pregnancy [ 9 ]. Coulam defines biochemical pregnancy when two or more increased values of hCG can be measured, yet there can be no evidence of gestational sac detected on transvaginal ultrasound 2 weeks later.…”
Section: Introductionmentioning
confidence: 99%
“…Due to variations in definitions for recurrent implantation failure and biochemical pregnancy, there is scarce data that accurately represents the incidence or prevalence. Biochemical pregnancy is actually not uncommon, and its reported incidence varies from 8 to 33% in the general population, including those who spontaneously conceived [ 9 ]. However, it is not clear how accurate these figures are since most patients who recognized that they had a biochemical pregnancy were undergoing ART.…”
Section: Introductionmentioning
confidence: 99%
“…One exception evaluated the etiology of RSA and considered the number of previous biochemical pregnancies (with groups defined as having experienced of 0 or 1 vs. more than 2). This study reported that spontaneous abortion with a normal karyotype occurred more frequently in the RBP experience group [ 10 ]. Unfortunately, no previous studies have explored the etiology of RBP in comparison to RSA after IVF.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that some potential causes of biochemical pregnancy include implantation failure due to chromosomal abnormalities and lack of endometrial receptivity due to anatomical, immunological or other reasons [ 11 ]. Another recent study, however, reported that biochemical pregnancy likely presents with similar etiology to that of recurrent spontaneous abortion (RSA) [ 10 ]. Unfortunately, the relatively small number of studies into these questions has left them unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…Incidence of implantation failures varies from 8 to 33% in the general population [1]. When conducting IVF/ET, pregnancy is established when an embryo, which is a semi-allograft, is successfully implanted to maternal decidua with an establishment of maternal immune tolerance [2].…”
Section: Introductionmentioning
confidence: 99%